The Implications of Religiosity and Complementary Determinants on the Repurchase Intention of Halal-Certified Food in Indonesia 2024 - Siregar, Jihan Luthfiyyah; Sobari, Nurdin (UI Scholars Hub, 2025)
Manuscript Type: Research Article. Research Aims: This study applies the Theory of Planned Behavior (TPB) framework to examine the impact of religiosity on repurchase intentions for halal-certified food, incorporating factors such as subjective norms, awareness, trust, halal knowledge, halal certification, and perceived behavioral control. Design/Methodology/Approach: Data were collected from 472 respondents through a purposive sampling survey in Indonesia, and analyzed using Structural Equation Modeling (SEM) with SmartPLS v.3.2.9. Research Findings: A total of 20 hypotheses were tested. The findings reveal that religiosity influences the mediators—halal knowledge, halal certification, subjective norms, and perceived behavioral control—which, in turn, shape attitudes and stimulate repurchase intentions. These four mediation paths are confirmed as integral to the underlying mechanism. However, the direct effects of trust and awareness on attitude, as well as their mediation paths, were not supported. Theoretical Contribution/Originality: The research expands the TPB by incorporating halal knowledge and certification as complementer determinants influencing repurchase intentions, offering a more comprehensive view of consumer behavior in the halal food sector in Indonesia. Practitioner/Policy Implication: Marketers and business owners selling halal-certified food should focus on educating and building trust, leveraging social influence, ensuring easy accessibility and competitive pricing, and differentiating while fostering emotional connections. Research Limitation/Implications: The study’s limitations include its focus on Indonesian Gen Z and millennial Muslims, which may restrict generalizability to other populations and regions, particularly given the predominantly female sample. Additionally, while the research centers on halal-certified food, other halal industries remain unexplored. Moreover, the study focuses on variables such as religiosity, awareness, and attitude, without addressing economic, marketing, or experiential factors. The survey method may also introduce response bias. Future research should broaden the demographic scope, include additional relevant variables, and adopt mixed methods to offer a more comprehensive understanding of consumer behavior in the halal market. Keywords: Halal certification, halal knowledge, religiosity, repurchase intention, TPB.